2020
DOI: 10.7554/elife.55547
|View full text |Cite
|
Sign up to set email alerts
|

Wiskott Aldrich syndrome protein regulates non-selective autophagy and mitochondrial homeostasis in human myeloid cells

Abstract: The actin cytoskeletal regulator Wiskott Aldrich syndrome protein (WASp) has been implicated in maintenance of the autophagy-inflammasome axis in innate murine immune cells. Here, we show that WASp deficiency is associated with impaired rapamycin-induced autophagosome formation and trafficking to lysosomes in primary human monocyte-derived macrophages (MDMs). WASp reconstitution in vitro and in WAS patients following clinical gene therapy restores autophagic flux and is dependent on the actin-related protein c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Some evidence suggests that actin may also be important in the late stage of phagosomal closure, as shown by the requirement for Arp2/3 during selective autophagy ( 79 ). More recently, Wiskott-Aldrich syndrome protein (WASp) has been linked to the global orchestration of both general and selective autophagy in myeloid cells ( 80 , 81 ). Even if a detailed mechanism of WASp-autophagy connections remains to be explored, it can be extrapolated that deregulation of actin dynamics (see below) will impact cGAS-STING signaling in phagocytes.…”
Section: Cgas-sting Trafficking and The Connection With The Cytoskeletonmentioning
confidence: 99%
See 2 more Smart Citations
“…Some evidence suggests that actin may also be important in the late stage of phagosomal closure, as shown by the requirement for Arp2/3 during selective autophagy ( 79 ). More recently, Wiskott-Aldrich syndrome protein (WASp) has been linked to the global orchestration of both general and selective autophagy in myeloid cells ( 80 , 81 ). Even if a detailed mechanism of WASp-autophagy connections remains to be explored, it can be extrapolated that deregulation of actin dynamics (see below) will impact cGAS-STING signaling in phagocytes.…”
Section: Cgas-sting Trafficking and The Connection With The Cytoskeletonmentioning
confidence: 99%
“…Compatibly with its abundance and the poor expression of the other NPFs, WASp was shown to multitask at the cell periphery and intracellularly in immune cells ( 80 , 118 ). WASp regulates multiple immune cell functions, ranging from BCR and TCR receptor signaling in lymphocytes to migration and phagocytosis in myeloid cells ( 81 ). Defects in these processes provide a logical explanation for weak responses to pathogens and increased susceptibility to infections.…”
Section: Actin-related Immunodeficiencies and The Link To Self-dna Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the WASP-ARP2/3 pathway appears crucial in the assembly of podosomes, while the WAVE complex is dispensable. Indeed both WASP and ARPC1B deficiencies are associated with the defective assembly of podosomes by monocyte-derived macrophages ( 19 , 84 ). In contrast, macrophages from Nckap1l -KO mice have a preserved ability to assemble podosomes although they display multiple defects in lamellipodia, focal adhesions and endocytosis ( 47 ).…”
Section: Motility Defects In Actinopathies At the Ultrastructural Levelmentioning
confidence: 99%
“…Reconstitution experiments in WAS patient-derived macrophages using micro-injections of full-length human WASP sequence suggested that the chemotactic response to the cytokine colony stimulating factor-1 is dependent on WASP-driven assembly of podosomes ( 159 ). To date, studies of WASP revealed its key role in podosome assembly in multiple cellular systems beyond macrophages: immature DCs ( 80 ), THP-1 ( 19 ) and T cells ( 89 ). Moreover, experiments using RNA interference to induce partial down-regulation of the intracellular WASP level in DCs led to compromised podosome formation ( 160 ), indicating that a precise regulation of WASP expression might be crucial for assembly of podosomes.…”
Section: Motility Defects In Actinopathies At the Ultrastructural Levelmentioning
confidence: 99%